2015
DOI: 10.18632/oncotarget.6723
|View full text |Cite
|
Sign up to set email alerts
|

CD147 regulates cancer migration via direct interaction with Annexin A2 and DOCK3-β-catenin-WAVE2 signaling

Abstract: The acquisition of inappropriate migratory feature is crucial for tumor metastasis. It has been suggested that CD147 and Annexin A2 are involved in regulating tumor cell movement, while the regulatory mechanisms are far from clear. In this study, we demonstrated that CD147 physically interacted with the N-terminal domain of Annexin A2 and decreased Annexin A2 phosphorylation on tyrosine 23. In vitro kinase assay showed that the I domain of CD147 was indispensable for CD147-mediated downregulation of Annexin A2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 52 publications
2
27
0
Order By: Relevance
“…Recently, the Rac1/WAVE2/Arp2/3 signaling pathway was reported to promote cell migration and invasion of glioma cells and liver cancer cells . The WAVE2/Annexin A2/DOCK3/β‐catenin signaling pathway promotes the invasiveness and metastasis of liver cancer cells . These findings indicated that WAVE2‐associated signaling pathways play important roles in cell invasion and metastasis in various types of cancer cells.…”
Section: Discussionmentioning
confidence: 92%
“…Recently, the Rac1/WAVE2/Arp2/3 signaling pathway was reported to promote cell migration and invasion of glioma cells and liver cancer cells . The WAVE2/Annexin A2/DOCK3/β‐catenin signaling pathway promotes the invasiveness and metastasis of liver cancer cells . These findings indicated that WAVE2‐associated signaling pathways play important roles in cell invasion and metastasis in various types of cancer cells.…”
Section: Discussionmentioning
confidence: 92%
“…Emerging evidence identified interaction of ANX A2 with Semaphorin 3D (sema3D) and CD147. Moreover, these interactions initiates DOCK3‐β‐catenin‐WAVE2 signaling leading to cell migration, invasion and metastasis . However, involvement of ANX A2 in these signaling pathways in vivo is yet to be established.…”
Section: Introductionmentioning
confidence: 99%
“…HFF-1 cells were obtained from American Type Culture Collection (ATCC, USA). A Huh-7 CD147-KO (Huh-7 CD147 −/− ) cell line was generated using a CRISPR/Cas9 system as previously reported [24]. All cells were cultured at 37℃, 5% CO 2 , in RPMI-1640 medium supplemented with 10% fetal bovine serum (FBS).…”
Section: Cell Linesmentioning
confidence: 99%